ЯКІСНИЙ АНАЛІЗМАТЕМАТИЧНИХ МОДЕЛЕЙ ПРОЦЕСІВ І ПРИСТРОЇВ ПЕРВИННОЇ ОБРОБКИ ВУГЛЕВОДНЕВОЇ СИРОВИНИ НА ОСНОВІ УЗАГАЛЬНЕНИХ МОДЕЛЕЙ - Polozhaenko, Sergey Anatolievich (Kamianets-Podilskyi National Ivan Ohiienko University, 2013)
Theorems of existence and uniqueness of the decision of system of the equations in the private derivatives, representing the generalized mathematical model of processes and devices of preprocessing of crude hydrocarbons are formulated and proved. Generalization gives the chance to apply the principle of unification and typification when developing a method of numerical realization of mathematical models of a class of processes (devices) of preprocessing of crude hydrocarbons, and the proof of the corresponding theorems (an essence ― the qualitative analysis) provides a correctness of application of the generalized model in applied problems of mathematical modelling of studied processes (devices). Proofs of the formulated theorems are strict, logically true and are consistently executed within terms of the functional analysis. Practical applicability of theorems of existence and uniqueness of the decision as component of the qualitative analysis, is defined by possibility of research on their basis of adequacy of algorithmic means of mathematical modelling of a studied class of processes (devices).